(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Poor agricultural reform management has resulted in dwindling fish yield along the Lake Basin in the country. To meet the ever-increasing demand for fish, fish farming as an alternative to artisanal fishery has become imperative. Hence, this paper examined how the limited variable inputs have been efficiently allocated to maximize the fish farmers’ productivity level in Kainji Lake Basin, Nigeria. Stratified and simple randomized sampling technique were used to select 204 respondents from the three main strata of Kainji Lake Basin. Primary data were sourced from both literate and illiterate fish farmers. Analytical techniques employed included descriptive statistics, partial and total factor productivity and Tobit regression models. The findings revealed that most of them used earthen ponds and sourced their fingelings from private hatcheries. The most bred fish were Clarias and Hetroclarias and were mostly harvested at six or seven months. In addition, majority of the farmers sourced water from river/streams and rainfall. The mean partial productivity result revealed that labour (38.12) and lime (31.00) were better utilized than feed, fertilizer, stocking density and pond size. The mean total factor productivity index of 2.36 showed that in the overall performance assessment, fish farmers were productive in the use of their resources. The significant determinants of culture fish farmers’ productivity included quantity of output (P < 0.01), quantity of feed (P < 0.05), stocking density (P < 0.01), labour (P < 0.05), educational level of fish farmers (P < 0.10) and access to credit (P < 0.10). High cost of feed and poor access to credit were the most severe constraints faced by the farmers. Based on the findings of this research, it is recommended that the Research Institute with Fresh water mandate should collaborate with skilled and adequately equipped extension agents to constantly educate the culture fish farmers on innovations in culture fish production that will improve their efficiency level. J Bangladesh Agril Univ 18(3): 680–687, 2020 https://doi.org/10.5455/JBAU.112941